THE EFFECT OF E-GOVERNMENT QUALITY (E-GOVQUAL) ON LOCAL GOVERNMENT E-GOVERNMENT USER SATISFACTION - Hakim, Moch. Lukmanul; Rahayu, Agus; Ahman, Eeng; Wibowo, Lili Adi (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
The measurement of E-Government user satisfaction at local governments in Indonesia still needs to be improved to achieve the high accountability demanded by the central government. Based on the theory of behavior, six factors influence the satisfaction of local government E-Government users, namely knowledge of ease of use, trust, function and form interaction, reliability, content and display of information, and support. This study examines the influence of these six factors on the E-Government Quality of local governments in the province of West Java. Respondents in this study were the head of the West Java regional government agency. This study uses PLS-SEM and succeeds in proving that there is a positive and significant effect of ease of use, trust, function and form interaction, reliability, content and display of information, and support for local government E-Government user satisfaction. These findings provide practical contributions as a guide for local governments to improve E-Government Quality. Future research needs to expand the scope of the observation area, incorporate subjective and objective scales of user satisfaction variables, and develop other variables based on other theories such as contingency theory, agency theory, and dynamic capabilities theory.